The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/00037028221091581
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Partial Least Squares-Discriminant Analysis Modeling for Accurate Classification of Edible Sea Salt Products Using Laser-Induced Breakdown Spectroscopy

Abstract: Laser-induced breakdown spectroscopy (LIBS) has been widely applied to material classification in various fields, and partial least squares-discriminant analysis (PLS-DA) is one of the frequently used classical multivariate statistics to construct classification models based on the LIBS spectra. However, classification accuracy of the PLS-DA model is sensitive to the number of classes and their similarities. Considering this characteristic of PLS-DA, we suggest a two-step PLS-DA modeling approach to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The two-step approach was previously applied to the sea salt classification problem with partial least squares discriminant analysis and found to be effective in increasing the classification accuracy particularly for the classes with minute differences. 33 The two-step LDA model was trained first to discriminate N1, N2, N5, N6, and the union of N3 and N4, and then the difference between N3 and N4 was separately modeled in the second stage. In this way, the minute difference between N3 and N4 could be more effectively exploited for modeling.…”
Section: Resultsmentioning
confidence: 99%
“…The two-step approach was previously applied to the sea salt classification problem with partial least squares discriminant analysis and found to be effective in increasing the classification accuracy particularly for the classes with minute differences. 33 The two-step LDA model was trained first to discriminate N1, N2, N5, N6, and the union of N3 and N4, and then the difference between N3 and N4 was separately modeled in the second stage. In this way, the minute difference between N3 and N4 could be more effectively exploited for modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the spectral lines Al( i ) (394.424 nm), Al( i ) (396.152 nm), Ca( i ) (422.672 nm) and P( i ) (253.561 nm) were highly ranked and contributed significantly to the model. In a similar approach, Park et al 114 analysed sea salt from Japan, Korea and France, establishing Ca, K and Mg as the key features for classification. It was observed that those with higher levels of Mg also tended to have higher signals for H( i ) at 656 nm due to the absorption of water linked with Mg salts such as MgSO 4 and MgCl 2 .…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%
“…In one by Park et al LIBS analysis was followed by a two-stage partial least squares discriminant analysis (PLSDA) to classify six commercial edible sea salt samples from three different countries (Japan, South Korea and France). 133 Although this is a fairly common approach during classification studies, this one had some novelty. In this study, the data were first sorted by the PLSDA into four classes and one extended class.…”
Section: Inorganic Chemicals and Materialsmentioning
confidence: 99%